2000
DOI: 10.3818/jrp.2.1.2000.87
|View full text |Cite
|
Sign up to set email alerts
|

Drunk Drivers, DWI “Drug Court” Treatment, and Recidivism: Who Fails?

Abstract: We conducted an evaluation of an experimental Driving-While-Intoxicated (DWI) Drug Court treatment program operated by a single municipal court. Specially trained court personnel assessed first-time (and, as we found out, some second-time) DWI offenders for symptoms of alcoholism. Once court personnel reached a clinical determination that an individual was an alcoholic, research team members randomly assigned that person to either the treatment program or to a control group receiving normal municipal court pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 6 publications
3
29
1
Order By: Relevance
“…The expedited processing DUI court examined in this study did not make use of enhanced alcohol and/or drug abuse treatment services, as would be expected as part of the treatment-oriented drug court model. The extant scientific literature on treatment-oriented DUI courts (those patterned after drug courts, and other problem-solving courts) also fails to provide evidence for the effectiveness of this model (i.e., treatment-focused courts following the drug court model; Bouffard & Richardson, 2007;Bouffard, Richardson, & Franklin, 2010;Breckenridge, Winfree, Maupin, & Clason, 2000;MacDonald, Morral, Raymond, & Eibner, 2007). While this pattern of results may suggest that DUI offenders are particularly intractable (not responding to deterrence or treatment-oriented interventions), it may also suggest that the models that have been applied to them so far are inappropriate.…”
Section: Discussionmentioning
confidence: 97%
“…The expedited processing DUI court examined in this study did not make use of enhanced alcohol and/or drug abuse treatment services, as would be expected as part of the treatment-oriented drug court model. The extant scientific literature on treatment-oriented DUI courts (those patterned after drug courts, and other problem-solving courts) also fails to provide evidence for the effectiveness of this model (i.e., treatment-focused courts following the drug court model; Bouffard & Richardson, 2007;Bouffard, Richardson, & Franklin, 2010;Breckenridge, Winfree, Maupin, & Clason, 2000;MacDonald, Morral, Raymond, & Eibner, 2007). While this pattern of results may suggest that DUI offenders are particularly intractable (not responding to deterrence or treatment-oriented interventions), it may also suggest that the models that have been applied to them so far are inappropriate.…”
Section: Discussionmentioning
confidence: 97%
“…One reported success in reducing alcohol-related offenses (Breckenridge, Winfree, Maupin, & Clason, 2000). The other reported no success, probably due to the lack of significant threatened jail time (MacDonald, Morral, Raymond, & Eibner, 2007).…”
Section: Transferability Of the Anchorage Wellness Court Modelmentioning
confidence: 99%
“…But some components of the DUI court were already mandated by statute, making it difficult to show differences between the DUI court and other DUI offenders. In an earlier study, researchers found statistically significant differences in recidivism measures between DUI court participants and control groups (Breckenridge, Winfree, Maupin, & Clason, 2000). Both of these studies involved low-level offenders who were offered very little legal incentive to inspire compliance.…”
Section: Replication and Institutionalizationmentioning
confidence: 99%
“…Breckenridge, Winfree, Maupin, and Clason (2000) reported that a DWI court program significantly reduces recidivism among alcoholic DWI offenders. Other studies of this type of program are currently underway and DWI courts are being implemented in numerous states.…”
Section: Drug/dwi Treatment Courtsmentioning
confidence: 99%
“…In particular, drug treatment courts and DWI courts use a structured series of incentives and sanctions, including jail time, to gain compliance with the courts' orders and have higher rates of treatment completion than traditional courts. Coerced treatment works and ultimately it is the best tool for reducing recidivism when dealing with an alcoholic/addict (Breckenridge et al, 2000;Freeman-Wilson & Wilkosz, 2002;Tauber & Huddleston, 1999).…”
Section: Traditional Sanctions For Dwi Offenses Imprisonmentmentioning
confidence: 99%